Layers of healing care - Shona Quin (Scottish Journal of Residential Child Care)
With growing pressure on child and adolescent mental health teams to meet the needs of young people in care, alongside limited resources, there is an increasing need for care settings to consider their role in providing trauma-informed, healing care environments. This article describes the process of developing a therapeutic framework within a small residential care setting in Scotland. The framework encapsulates the importance of attending to the needs of the organisation as a whole in order to provide a safe, attuned and responsive environment, highlighting the fundamental layers of care necessary to provide a foundation upon which the healing journey can begin.